Maternal Factors on Stunting in Pekanbaru Local Health Center, Indonesia: Faktor Ibu Pada Stunting di Puskesmas Pekanbaru, Indonesia - Winda Septiani; Elly Satriani Harahap; Hetty Ismainar; M Kamali Zaman; Agus Alamsyah; Riri Maharani (Universitas Muhammadiyah Sidoarjo, 2020)
Stunting is a health problem by multiple factors (Mother factor, socio-economic factor). The growth retardation (stunting ) was measure by height for age scale which primarily indicates chronic undernutrition. In 2018, the prevalence of stunting in Riau province was 35%, which was higher than the national prevalence of 30.8%. This was an quanitative with cross sectional analytic deign. The study was conducted in Puskesmas Harapan Raya Pekanbaru, Riau, Indonesia. The population was all children (4000), sampel was 187 children by systematic random sampling. Research was to analyze independents variable (risk of stunting) to the dependent’s variable (mother’s age, Prity, Mother Parity, Mother’s Height, (Lila) / MUAC (Mid Upper Arm Circumference), Maternal Characteristics (hemoglobin), Tension Mother’s, ANC Visit, Dietary habit, Mother’s child care, Completed immunization, Weight child and Drink for child.) Research results is maternal hemoglobin ​​in pregnancy with a risk category of having a stunting 53.4%, exlusive breastfeeding with a risk category of having a stunting 54.1%, dietary habit with a risk category of having a stunting 51.3%. Independents variable (Maternal Characteristics (hemoglobin), Exclusive Breastfeeding, Dietary Habis), is a significant association to stunting. The findings from this study will be helpful for programmatic intervention to reduce the stunting.